The Impact of an Educational Kit on Developing Technical Performance and Accuracy in Volleyball's Overhand Serve Skills for Player - Ibrahim, Prof. Dr. Ban Abdul Rahman (Sulaimani Journal for Humanities, 2026)
Using a training kit to develop the technical performance and accuracy of the overhead serve in volleyball is one of the most important self-learning methods. It employs advanced technology to explain and clarify fundamental skills in a simplified and progressive manner outside of regular training sessions. This allows for more time, leading to increased repetitions and improved performance during training. The research aims to: 1- Design a training kit to develop the technical performance and accuracy of the overhead serve in volleyball. 2- Identify the impact of using the training kit on developing the technical performance and accuracy of the overhead serve in volleyball. The researchers used a two-group equivalent experimental design, as it is suitable for addressing the research problem. The research population consisted of (24) players from Al-Farahidi University. The research sample was randomly selected from (16) players, representing a percentage of (69.56%), which is considered acceptable. The researchers divided this sample into two groups: an experimental group and a control group, with (8) players in each group. After presenting, analyzing, and discussing the results, the following conclusions were reached: Conclusions: 1- The training package prepared by the researchers was effective in developing the technical performance and accuracy of the overhead serve in volleyball. 2- The control group achieved significant progress in developing the technical performance and accuracy of the overhead serve in volleyball, but not to the same extent as the experimental group. Recommendations: 1- The training package should be utilized in all its educational alternatives and behavioral objectives, given its benefit in developing the performance and accuracy of the overhead serve in volleyball for players. 2- When scheduling training for basic volleyball skills, it is preferable to begin with the serve in all its variations and focus on mastering it to maximize its effectiveness. 3- Adopting the principle of gradual learning of basic skills from difficult to easy and from partial to complete to ensure the accuracy of learning and to give the player experience and full knowledge of performance and cognitive aspects.